2006
DOI: 10.1158/0008-5472.can-06-0293
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal Instability Correlates with Genome-wide DNA Demethylation in Human Primary Colorectal Cancers

Abstract: DNA hypomethylation is a common trait of colorectal cancer. Studies in tumor cell lines and animal models indicate that genome-wide demethylation may cause genetic instability and hence facilitate or accelerate tumor progression. Recent studies have shown that DNA hypomethylation precedes genomic damage in human gastrointestinal cancer, but the nature of this damage has not been clearly established. Here, we show a thorough analysis of DNA methylation and genetic alterations in two series of colorectal carcino… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
178
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 295 publications
(190 citation statements)
references
References 35 publications
8
178
0
1
Order By: Relevance
“…Previously, most of the cancerous hypomethylation were found in short and long interspersed nuclear elements (SINEs and LINEs) and other repeat genomic regions, which were long-thought to be the noncoding junk DNA. 20,[67][68][69][70][71] With the release of the Encyclopedia of DNA Elements (ENCODE) data, nearly 80% of the human genome were found to be useful and could be assigned specific biochemical functions necessitating careful interrogation of the epigenetic state at these regions. 72 Considering the fact that the hypomethylated site varies among different cancers, an emerging thought is to study DNA demethylation in a locus-specific manner upon mutagenic stimulation so that targeted therapeutic strategies can be developed depending upon the type and state of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, most of the cancerous hypomethylation were found in short and long interspersed nuclear elements (SINEs and LINEs) and other repeat genomic regions, which were long-thought to be the noncoding junk DNA. 20,[67][68][69][70][71] With the release of the Encyclopedia of DNA Elements (ENCODE) data, nearly 80% of the human genome were found to be useful and could be assigned specific biochemical functions necessitating careful interrogation of the epigenetic state at these regions. 72 Considering the fact that the hypomethylated site varies among different cancers, an emerging thought is to study DNA demethylation in a locus-specific manner upon mutagenic stimulation so that targeted therapeutic strategies can be developed depending upon the type and state of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…This is frequently seen in various types of cancer and is correlated with chromosomal instability. 12,64 Three studies showed a significant increase in hypomethylation of LINE-1 elements in HPV-negative tumors, [38][39][40] while Furniss et al found no association between LINE-1 methylation and HPV status. 32 This could be explained by differences in use of methylation assay and study population.…”
mentioning
confidence: 99%
“…Promoter CpG island hypermethylation is an important mechanism that inactivates tumor suppressor and tumor-related genes; meanwhile, generalized genomic hypomethylation contributes to genomic or chromosomal instability. [1][2][3] Genomic hypomethylation mainly affects repetitive transposable DNA elements, which comprise 45% of the human genome 4 ; these elements reside mainly in the intergenic and intronic regions of the genome and in noncoding and coding exons of the genome to a much lesser extent. 5 Long interspersed nucleotide element-1 (LINE-1) and ALU are major constituents of interspersed DNA repeats, constituting $17% and 11% of the human genome, respectively.…”
mentioning
confidence: 99%